The Place of Manager in Administration of Organization ("Journal "U". Economy. Management. Finance.", 2017)
The article is devoted to the review of main conceptions of the role of manager in organization administration. The author gives conclusions about reasons of success of effective managers
Keywords: management; manager; administration of organization